Analysis of Traffic Volume Due to the Sound of Motor Vehicle in front of SMA Taruna Terpadu Boash During Covid-19 - Syaiful, Syaiful; Shinta Aminda, Renea; Rulhendri, Rulhendri; Haldiana, Haldiana (ASTONJADRO, 2022)
Each motorized vehicle produces a variety of noise. This noise has a considerable impact on the tranquility of the area that is directly in contact with the highway. Therefore, setting the distance between the main school building and the highway must be taken into account, for the sake of realizing the comfort of the school students. The volume of motorcycles, the volume of private vehicles and public transportation has a significant effect on noise, from all the analysis calculations, the largest equation is obtained on the first day of the study, the third point (Sound Level Meter 3) a distance of 20.50m, with the calculation below, y = 54 .61 + 0.002x1 – 0.002x2 + 0.002x3 + 0.004x4. This equation means that if there is no decrease in the volume of the motorcycle, the noise level at SLM3 is 55.21 dBA. If there is an increase and decrease in the volume of the motorcycle it will have a significant effect on the noise. The second largest equation in the second day of research is at the second point (Sound Level Meter 2) a distance of 4.00m with an equation calculation of, y = 57.22 - 0.012x1 - 0.021x2 - 0.022x3 - 0.014x4. The meaning of the above equation is that if there is an increase in the volume of the motorcycle, the noise in SLM2 is 57.22dBA. From the results obtained, there was a reduction in the number of motorbikes during the Covid-19 pandemic, because students who were studying did not come to school. The reduction in the number of motorbikes crossing the SMA Taruna Terpadu Boash reached 52%.